Parameters of glycemic variability in continuous glucose monitoring as predictors of diabetes: a prospective evaluation in a non-diabetic general population - Rodríguez García Javier; Camiña Darriba Felix; Ortolá Devesa Juan B.; Rodríguez-Segade Villamarín Santiago; Valle Rodríguez Andrea (Advances in Laboratory Medicine)
To prospectively examine the ability of some glycemic variability metrics from continuous glucose monitoring (CGM) to predict the development of diabetes in a non-diabetic population.